2014
DOI: 10.1097/ta.0b013e3182ab0cfc
|View full text |Cite
|
Sign up to set email alerts
|

Are we delivering two standards of care for pelvic trauma? Availability of angioembolization after hours and on weekends increases time to therapeutic intervention

Abstract: Therapeutic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 27 publications
3
73
0
2
Order By: Relevance
“…Mortality rates for patients with pelvic fracture presenting with hemodynamic instability range between 21% and 50% in contemporary published series. 1,2,11,16,17 In this series of patients, injury severity was high in patients with pelvic fracture admitted in shock (mean ISS, 28.2), and associated injuries were common as demonstrated by a substantial number of patients with head, chest, and abdomen AIS scores of 3 or higher. These associated injuries may also require urgent operative intervention for hemorrhage control and may further influence the decision of the trauma surgeon to treat the patient in the operating room versus the IR suite.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Mortality rates for patients with pelvic fracture presenting with hemodynamic instability range between 21% and 50% in contemporary published series. 1,2,11,16,17 In this series of patients, injury severity was high in patients with pelvic fracture admitted in shock (mean ISS, 28.2), and associated injuries were common as demonstrated by a substantial number of patients with head, chest, and abdomen AIS scores of 3 or higher. These associated injuries may also require urgent operative intervention for hemorrhage control and may further influence the decision of the trauma surgeon to treat the patient in the operating room versus the IR suite.…”
Section: Discussionmentioning
confidence: 95%
“…A study by Eastridge et al 18 found that hypotensive patients with unstable pelvic fracture patterns were more likely to have hemorrhage from a pelvic source, suggesting that initial interventions should focus on angiography before laparotomy. The importance of prompt access to therapeutic angioembolization was demonstrated by Schwartz et al 11 who reported that the time to IR was significantly increased during night hours and weekends compared with daytime hours. It is important to note that on multivariate regression analysis, they found that treatment on nights and weekends was associated with a near 100% increase in 30-day mortality, highlighting the importance of prompt intervention for patients with pelvic hemorrhage.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Pelvic bleeding after blunt trauma has traditionally been difficult to control surgically. Although recent reports have documented success with preperitoneal packing of pelvic bleeding, 46,47 angiographic embolization of pelvic bleeding has become a mainstay for definitive control of massive pelvic bleeding [48][49][50] after blunt trauma. This technique of angiographic embolization of pelvic bleeding currently requires fluoroscopy.…”
Section: Damage Control Resuscitationmentioning
confidence: 99%
“…Se debe intentar afinar más en los resultados del trauma y la atención recibida 58,59 y no limitarse solo a la estancia hospitalaria y mortalidad intrahospitalaria, buscando incluir como resultados la mortalidad a un tiempo determinado tras el alta hospitalaria, resultados funcionales, retorno a las actividades previas y calidad de vida.…”
Section: Futuro De Los Registros De Traumaunclassified